Penatalaksanaan Fisioterapi pada Kasus Post OP Rekontruksi Anterior Cruriate Ligament Fase 1 Dextra dengan Terapi Latihan - Muhammad Hanif Mardiansyah; Maya Triyanita (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
ACL injury is one of the injuries that many athletes experience. One of them is basketball athletes. This happens because basketball sports have a lot of movements - speed movements, changing direction, jumping and landing. Efforts to treat total ACL rupture injuries are by reconstruction. The physiotherapy program after ACL reconstruction uses a special exercise therapy protocol including phase 1, phase 2, phase 3 and phase 4. In phase 1, exercise therapy aims to reduce pain, oedema, increase LGS and muscle strength. The research method used is a single - case study of a 19-year-old male patient who suffered a right knee ACL reconstruction injury with exercise therapy in the form of Quad Set, Straight Leg Raise (SLR), Heel Slide, Wall Slide, and Angkle Pump. After the therapy was carried out for 4x, the results were reduced pain from VAS 3 to 1, increased stiffness of the Flexor knee muscle from 100 mmHg to 160 160 mmHg and the Extensor knee muscle from 120 mmHg to 160 mmHg, and increased the scope of active joint motion of knee flexion from 100 ° to 130 ° and knee extension from 110 ° to 135 °. Phase 1 Exercise Therapy Management in patients with Post Reconstruction of ACL knee destra can reduce pain, increase muscle strength, and increase the scope of joint motion.